Strategi Pengembangan Padi Lokal Kalimantan Utara - Rudy Firyanto; Mardhiana (Universitas Wahid Hasyim, 2025)
Adan rice is a traditional rice variety grown by the Dayak community in Krayan District, Nunukan Regency, North Kalimantan. The advantages of Adan rice include its distinctive aroma, soft texture, and high adaptability to highland environments. Agriculture in Krayan is still based on local wisdom, utilizing buffalo labor and organic fertilizers, as well as post-harvest practices closely tied to traditional customs. However, Adan rice farming faces various challenges, such as limited market access due to geographical isolation, inadequate infrastructure, limited farmer capital, and competition with cheaper non-organic rice. This research seeks to explore both the difficulties and possibilities in the development of Adan rice and formulate strategies based on local wisdom to improve its productivity and competitiveness. A SWOT analysis assesses the internal and external influences on Adan rice cultivation. The analysis results indicate that applicable strategies include enhancing farmers' capacity through training, strengthening farmer institutions, diversifying Adan rice-based products, and utilizing information technology to expand market access. By implementing the right strategies, the sustainability of Adan rice farming can be maintained, farmers' welfare can be improved, and product competitiveness in both local and international markets can be strengthened. Support from the government and various stakeholders is crucial in optimizing the management and marketing of Adan rice in the future.